Composition of gillnet catches based on network size at UPT Fishery Port of Riau Province - Hasibuan, Siti Hawa; Yani, Alit Hindri; Nofrizal, Nofrizal (Science, Technology, and Education Care, 2024)
Gill net catches are one of fishermen's dominant fishing gear at UPT Dumai City Fishing Port. Gill net catches are easy to operate, have a low price, and are durable. This research was conducted in July-August at UPT Port of Fisheries, Riau Province. This study aimed to determine differences in gill net catches based on different mesh sizes. The method used is the survey method. The catch of gill nets by type with a mesh size of 2 inches is 25 fish species. Based on the weight and number of individual fish, it was dominated by lomek (Harpodon sp), namely 1,359.5 kg or 21.5% and 16,314 individuals or 27.18%. The catch in the 3-inch mesh size was 23 species of fish. The percentage of catches based on weight dominated by senangin (Eleutheronema tetradactylum) was 30.38% (1,353.5 kg), and based on the number of individuals dominated by pomfret of 18.72% (4,534 individuals). The main catches in gill nets at UPT Dumai are lomek (Harpodon sp), senangin (Polynemus sp), pomfret (Bramidae sp) and machete (Chirocentrus sp). The primary and bycatch yields for the 2-inch mesh were 51.58% and 42.42%, while the 3-inch mesh sizes were 57.99% and 42.01%.